1970
DOI: 10.1071/ea9700099
|View full text |Cite
|
Sign up to set email alerts
|

Response to salinity in Glycine. 4. Salt concentration and the content of phosphorus, potassium, sodium and chloride in cultivars of G. wightii (G. javanica)

Abstract: Adaptability to salinity stress was related to the productivity of Glycine wightii (G. javanica) cultivars by the technique of comparing the multivariate characteristics of response for 22 accessions that are representative of the world centres of origin. Roots and tops responses were compared to clarify the metabolic relations between glycines, as salinity was increased from that required for normal growth and metabolism to levels almost causing death due to excess sodium chloride in the substrate. There was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1973
1973
1986
1986

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…The selected age and level of phosphorus nutrition were found favourable in previous studies for the growth of L. hainesii (Gates et al 1973) and for S. humilis (Gates et al 1966).…”
Section: Introductionmentioning
confidence: 98%
See 4 more Smart Citations
“…The selected age and level of phosphorus nutrition were found favourable in previous studies for the growth of L. hainesii (Gates et al 1973) and for S. humilis (Gates et al 1966).…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies in this laboratory (Gates et al , 1973 have suggested strongly that, in interspecific studies of response to stress, little interest resides in any individual variate. Although small differences between species for individual variates can be detected, the overall comparison is more meaningful when considered as an integrated set of such small differences.…”
Section: (B) Numerical Analysesmentioning
confidence: 99%
See 3 more Smart Citations